Pyrolysis temperature regulates sludge-derived biochar production, phosphate adsorption and phosphate retention in soil. Issue 3 (June 2022) - Liang, Jinsong; Ye, Junpei; Shi, Chuan; Zhang, Panyue; Guo, Jianbin; Zubair, Mohammad; Chang, Jianning; Zhang, Lian
Abstract: Biochar production from sewage sludge for phosphate adsorption provides a new route for treatment and reutilization of sewage sludge. The effect of pyrolysis temperature from 300 to 750 ℃ on sludge-derived biochar properties and their phosphate adsorption capacities were investigated. The biochar production decreased with increasing the pyrolysis temperature because of the loss of element C, H, and N during pyrolysis process. Ca, Mg, Al, Fe, and heavy metals (Cu, Zn, Ni, and Pb) were accumulated with increasing pyrolysis temperature. The sludge-derived biochar prepared at 300 ℃ was acidic while those at a pyrolysis temperature higher than 300 ℃ were alkaline. Increasing pyrolysis temperature led to fewer aliphatic functional groups and more aromatic structures in sludge-derived biochar. Phosphate adsorption capability increased with increasing pyrolysis temperature, and the maximum adsorption capability was 5.93 mg/g (as P) when the pyrolysis temperature was 700 ℃. The adsorption results were excellently fitted by Langmuir model, and monolayer phosphate adsorption capability of B700 was 5.469 mg/g. Change in surface area, charge, and functional groups were not the key reasons for enhancing the phosphate adsorption by sludge-derived biochar. The precipitation of phosphate with exchangeable Mg might be the dominating mechanism for phosphate adsorption due to a high exchangeable Mg content of 512.9 mmol/kg at 700 ℃. After soil column leaching for 42 d, the cumulative phosphate leaching loss with 3% B700 was only 20.60 μg/g, realizing an excellent effect of phosphate retention. These findings provide the theoretical basis for sewage sludge recycling as soil amendment. Graphical Abstract: ga1 Highlights: Biochar yield decreased with increasing the pyrolysis temperature. Phosphate adsorption capacity of biochar (B700) reached the maximum of 5.93 mg P/g. Interaction between phosphate and exchangeable Mg may be mainly adsorption mechanism. B700 reduced phosphate leaching loss and improved phosphorus retention in soil matrix.